Parallel strategies analysis over the HEVC encoder - Piñol, P.; Migallón, H.; López-Granado, O.; Malumbres, M. P. (The Journal of supercomputing, 2014)
Recently, a new video coding standard called HEVC has been developed to deal with the nowadays media market challenges, being able to reduce to the half, on average, the bit stream size produced by the former video coding standard H.264/AVC at the same video quality. However, the computing requirements to encode video improving compression efficiency have significantly been increased. In this paper, we focus on applying parallel processing techniques to HEVC encoder to significantly reduce the computational power requirements without disturbing the coding efficiency. So, we propose several parallelization approaches to the HEVC encoder which are well suited to multicore architectures. Our proposals use OpenMP programming paradigm working at a coarse grain level parallelization which we call GOP-based level. GOP-based approaches encode simultaneously several groups of consecutive frames. Depending on how these GOPs are conformed and distributed, it is critical to obtain good parallel performance, taking also into account the level of coding efficiency degradation. The results show that near ideal efficiencies are obtained using up to 12 cores.